2007
DOI: 10.1016/j.physbeh.2006.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral damage to the sexually dimorphic medial preoptic area/anterior hypothalamus of male ferrets causes a female-typical preference for and a hypothalamic Fos response to male body odors

Abstract: Previous studies showed that bilateral lesions of the male ferret's preoptic area/anterior hypothalamus (POA/AH), centered in the sexually dimorphic nuclei present in this region, caused subjects to seek out a same-sex male, as opposed to a female conspecific. Male subjects with POA/AH lesions (which were also castrated and given estradiol) displayed female-typical receptive behavior in response to neck gripping by a stimulus male, implying that subjects' approaches to a same-sex conspecific were sexually moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…of neurons in the POA/AH, male subjects would display the default, female-typical preference to seek out male odors. This hypothesis was confirmed in a study (Alekseyenko et al, 2007) showing that bilateral lesions of the male nucleus of the POA/AH in male ferrets caused them to prefer to approach volatile body odors from other male ferrets. These lesioned ferrets also showed a female-like profile of rostral medial POA Fos responses to volatile male odors.…”
Section: Sex Differences In Sexual Partner Preference: Contribution Omentioning
confidence: 61%
“…of neurons in the POA/AH, male subjects would display the default, female-typical preference to seek out male odors. This hypothesis was confirmed in a study (Alekseyenko et al, 2007) showing that bilateral lesions of the male nucleus of the POA/AH in male ferrets caused them to prefer to approach volatile body odors from other male ferrets. These lesioned ferrets also showed a female-like profile of rostral medial POA Fos responses to volatile male odors.…”
Section: Sex Differences In Sexual Partner Preference: Contribution Omentioning
confidence: 61%
“…Lesions of the mPOA diminish preference for a female partner in rats and ferrets [7,65,105,106], decrease pursuit of the female by male rats [104], and decrease anticipatory erections and anogenital investigations in marmosets [91]. Furthermore, in vivo dialysis experiments have revealed that sexual interactions progressively increase the level of extracellular dopamine in the mPOA of male rats and this increase begins as soon as the male is introduced to the female and initiates pursuits and anogenital investigations, i.e., several minutes before the beginning of copulatory interactions (consummatory responses) sensu stricto [79].…”
Section: The Medial Preoptic Area Is Also Implicated In the Control Omentioning
confidence: 99%
“…Another group reported that SDN-POA lesions in male rats decreased the percentage of animals that ejaculated in a mating test, and increased latencies to mount, intromit, or ejaculate [41]. Although an exact homolog of the SDN-POA may not exist in other species, there is evidence for sexual dimorphism of the anterior hypothalamus and preoptic area in other species that have been studied [152,22,111,2], making the SDN-POA of the rat a valuable comparative model.…”
Section: Sexually Dimorphic Nucleus Of the Preoptic Area (Sdn-poa)mentioning
confidence: 99%